MicroRNA Regulation of the Environmental Impact on Adolescent Neurobehavioral Development: A Systematic Review - Vázquez-Ágredos, Ana; Gámiz, Fernando; Gallo, Milagros (Frontiers in Cellular Neuroscience, 2022)
Adolescence is a late developmental period marked by pronounced reorganization of brain networks in which epigenetic mechanisms play a fundamental role. This brain remodeling is associated with a peculiar behavior characterized by novelty seeking and risky activities such as alcohol and drug abuse which is associated with increased susceptibility to stress. Hence, adolescence is a vulnerable postnatal period since short- and long-term deleterious effects of alcohol drinking and drug abuse are serious worldwide public health. Among several other consequences, it has been proposed that exposure to stress, alcohol or other drugs disrupts epigenetic mechanisms mediated by small non-coding microRNAs (miRNAs). During adolescence this modifies the expression of a variety of genes involved in neurodevelopmental processes such as proliferation, differentiation, synaptogenesis, neural plasticity and apoptosis. Hence, the effect of miRNAs dysregulation during adolescence might contribute to a long-term impact on brain function. This systematic review focus on the miRNAs expression patterns in the adolescent rodent brain with special interest in the impact of stress and drugs such as amphetamine, cocaine, nicotine, cannabis and ketamine. The results point to a relevant and complex role of miRs in the regulation of the molecular processes involved in adolescent brain development as part of a dynamic epigenetic network sensitive to environmental events with distinctive changes across adolescence. Several miRs have been assessed evidencing changing expression profiles during the adolescent transition which are altered by exposure to stress and drug of abuse. Since this is an emerging rapidly growing field, updating the present knowledge will contribute to improve our understanding of the epigenetic regulation mechanisms involved in the neurodevelopmental changes responsible of the adolescent behavior. It can be expected that increased knowledge of the molecular mechanisms mediating the effect of environmental threats during the adolescent critical developmental period will improve understanding psychiatric and addictive disorders emerging at this stage.